Performance evaluation of biofil toilet waste digester technologies in Ghana: the efficacy of effluent treatment options. Issue 23 (1st December 2016) - Amoah, Philip; Gbenatey Nartey, Eric; Schrecongost, Alyse
ABSTRACT: The study was carried out to assess the efficacy of a standard Biofil toilet digester with regard to its effluent quality and to evaluate the performance of new effluent polishing options being developed by BiofilCom. Influent and effluent were collected from 18 standard Biofil digesters connected to full-flush toilets. Effluent from five pilot installations with improved effluent polishing options were also taken for analyses. Ten other Biofil installations were selected to assess the impact of digester effluent discharge on the surrounding soil. Pollutant concentrations in the Biofil effluent exceeded both Ghana EPA and WHO standards for discharge though pollutant removal efficiencies were high: 84% for biochemical oxygen demand, 86.1% for chemical oxygen demand and 82.4% for total suspended solids. Escherichia coli and total coliform levels were significantly reduced by 63% and 95.6%, respectively, and nutrients were the least removed from effluents. Generally, effluents from the majority of the pilot polishing options met most of the discharge standards. E. coli were present in the soil at all study sites, except one. Biofil digester effluent is discharged subsurface but comparing their effluent quality with standards for discharge into water courses is relevant especially in areas of frequent flooding and high water tables.